b/3b=5(2-b)-4(1-3b)*

Simple and best practice solution for b/3b=5(2-b)-4(1-3b)* equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b/3b=5(2-b)-4(1-3b)* equation:



b/3b=5(2-b)-4(1-3b)*
We move all terms to the left:
b/3b-(5(2-b)-4(1-3b)*)=0
Domain of the equation: 3b!=0
b!=0/3
b!=0
b∈R
We add all the numbers together, and all the variables
b/3b-(5(-1b+2)-4(-3b+1)*)=0
We multiply all the terms by the denominator
b-((5(-1b+2)-4(-3b+1)*))*3b=0

See similar equations:

| 3x-8+x=4x-8 | | 4x-8+x=4x-8 | | 6t=42t= | | (x-3)/5+4=0,2x+6 | | 5x+17=11x-5 | | 6r+11=3r+2* | | 3x-2=12x-93 | | 2(n+1)=8n-1 | | 5x+36=12x+1 | | 4(6x–7)=144 | | 4(m+2)=6m-3 | | 3x-11=3x-1 | | 8x-37=3x-7 | | 3(x-5)=7+12 | | 2x−1=4x+2 | | 3-2x=0,333333333333333333333333333333333(x+2) | | -5+4g+g=10 | | 3-2x=0,33(x+2) | | 3-2x=(1/3)(x+2) | | -24.4b=14.4 | | 18-4a=5a | | -2x-4=3x+31 | | 5z+6=–9 | | 2(x-2)=6-3(x+5) | | 2(4x+5)=2x+4 | | 3=20+4c | | 8c+3c=2c-5c | | 8(5^(x+3))–54=146 | | 3d-d=2d+4d | | 10/4=n/8 | | 3y+4=y+4 | | 3x4=-12 |

Equations solver categories